2017
DOI: 10.1016/j.mechmachtheory.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the power and energy consumption of powered prosthetic ankles with series and parallel elasticity

Abstract: Several works have shown that series and parallel elasticity can reduce peak power and energy consumption in prosthetic ankles. Setting the right stiness of the elastic elements is essential to unlock this potential. In this work, we perform a thorough optimization of series and parallel elastic elements for a prosthetic ankle driven by a geared DC motor. Through simulation, we study the eect of drivetrain limitations and compare dierent mechanical and electrical optimization objectives. The results highlight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…That is: (12) where n = n(θ 0 ) from the rolling contact constraints (Equations (6) and 7). Therefore, using this relationship and Equations (10) and (11), a single nonlinear equation in θ 0 is obtained, which can be solved using a tool such as Matlab's fsolve or a custom line search. Additionally, parameters a and b can be found by this process.…”
Section: Numerical Solution Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…That is: (12) where n = n(θ 0 ) from the rolling contact constraints (Equations (6) and 7). Therefore, using this relationship and Equations (10) and (11), a single nonlinear equation in θ 0 is obtained, which can be solved using a tool such as Matlab's fsolve or a custom line search. Additionally, parameters a and b can be found by this process.…”
Section: Numerical Solution Methodsmentioning
confidence: 99%
“…The following abbreviations are used in this manuscript: End deflections a and b presented in Equations (10) and (11) of Section 3.2 are defined by using a set of homogeneous coordinate transformations (translation and rotation), which is presented in the following:…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that adding an active element in prosthesis can aid in attaining the similar energy as if in the real limb and reduced metabolic cost but somehow it increases the weight that is also correspond to added energy during walking and resulting in asymmetric gait [29]. In order to prevent these comorbidities, many researches have been done to investigate the series and parallel elasticity for power amplification and energy storage and at the same time reduces the actuation unit weight as shown in Figure 2 [30]. Addition of series and parallel elasticity can reduce the peak power and reducing the torque values where reducing the energy consumption at the same time [31].…”
Section: Current Researchesmentioning
confidence: 99%
“…Addition of series and parallel elasticity can reduce the peak power and reducing the torque values where reducing the energy consumption at the same time [31]. Addressing motor design, gearbox and springs and studying the operating range for each component in the actuated prosthesis is necessary to reduce the energy consumption, perform a better dynamic response, reduce size and weight [30].…”
Section: Current Researchesmentioning
confidence: 99%